5((7x-2)-14x+4=
3 answers
Sorry, but the equation you provided is incomplete. Could you please provide the complete equation?
what is 5 (7x-2) -14x+4
To simplify the expression 5(7x-2) - 14x + 4, we can use the distributive property.
First, let's distribute the 5 to each term inside the parentheses:
5 * 7x = 35x
5 * -2 = -10
Now the expression becomes:
35x - 10 - 14x + 4
Next, we can combine like terms:
(35x - 14x) + (-10 + 4) = 21x - 6
Therefore, the simplified expression is 21x - 6.
First, let's distribute the 5 to each term inside the parentheses:
5 * 7x = 35x
5 * -2 = -10
Now the expression becomes:
35x - 10 - 14x + 4
Next, we can combine like terms:
(35x - 14x) + (-10 + 4) = 21x - 6
Therefore, the simplified expression is 21x - 6.